Social theory of risk, a deliberation from urban studies: relationship society and territory - García-Hernández, Dalila (2023)
The changes that occur in contemporary society manifest the complexity of its constructions, reflected in the different risks, consequence of human actions and the management of natural resources, that is why the objective of the article is to analyze the social theory of risk considering the relationship between society and territory in the framework of urban studies. It is presented in a conceptual theoretical discussion from the critical analysis of various authors, gaining relevance by showing the way in which actions generate a transformation through the creation and reproduction of situations that are built under vulnerability scenarios in the territory considering the relationship with society. It is concluded that, with respect to social phenomena and their territorial components, the relationship between society and territory responds to a dynamic in the determinants of the development of the social theory of risk, facilitating the understanding of human action.